Aplikasi SIG Untuk Pemetaan Sebaran Tambak di Kecamatan Jawai, Kecamatan Sambas - Nur Ervina Meylani (PAKIS JOURNAL INSTITUTE, 2023)
The Fish pond is one of the artificial habitats used as a place for marine and brackish culture which is located in the coastal area and always undergoes a change of area with each change of time. Changes in the area of the debris can be caused either by nature or by human. Changes in the area of this pile may be either the opening of the pile or the transfer of the functions of a pile. Jawai District itself is one of the sub-districts in the Sambas Regency area that has embankment area. So the aim of this research is to map the distribution of fish pond area in Jawai District as a form of GIS application. GIS itself can simply be interpreted as a data processing application that can process spatial data. And the data input from this study is Landsat 8 satellite images of 2013, 2016, 2019 and 2022. The result of the data processing was obtained that the area of the Jawai district is spread out in 5 villages namely Lambau, Sarang Bird Danau, Sarang Burung Kuala, Sarang Burung Usrat, and Sungai Nilam. The largest embankment area is in Sarang Burung Danau Village, namely 776,521 ha and the lowest is in Lambau Village, namely 18,119 ha.